Dynamic Behavior of Masonry Houses Retrofitted by Bamboo Band Meshes - Meguro, K.; Soti, R.; Sathiparan, N.; Numada, M. (My University, 2012)
The collapse of unreinforced masonry structures, which are widely distributed around the earthquake prone regions of the world, is one of the greatest causes of death in major earthquake disasters. This paper presents an innovative retrofitting method for masonry structures, which uses bamboo band arranged in a mesh fashion and embedded in a mortar overlay. In order to evaluate the effectiveness of the proposed retrofitting technique, shake table tests were conducted using retrofitted and non-retrofitted 1/4 scaled masonry houses with sinusoidal ground motion inputs. Based on the experimental results, the retrofitted specimen exhibited good seismic performance withstanding over twice larger input energy than what non-retrofitted specimen could do.
Keywords: unreinforced masonry; bamboo-band mesh